The relationship of quality performance appraisal experience on job satisfaction and organizational commitment / Nurul Hazlin Ismail - Ismail, Nurul Hazlin (Faculty of Business and Management, 2013)
The purpose of this paper is to examine the relationship between quality performance appraisal experience on job satisfactions and organizational commitment at Grand Banks Yachts. In order to identify the relationship between quality performance appraisal experience with job satisfaction and organizational commitment, 159 sets of questionnaire has been distributed to the Grand Banks Yachts workers. Based on the research objectives and research questions that had been developed, the findings showed that the employee's job satisfaction and organizational commitment had been increased when the organization adapt the performance appraisal into the working environment. This study has resulted that quality performance appraisal experience are positively associated to job satisfaction an organizational commitment. This study also illustrates several recommendations for future research.